2019
DOI: 10.1186/s12884-019-2682-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of stillbirth in Nigerian referral hospitals: a multicentre study

Abstract: BackgroundIn 2015, Nigeria’s estimated 317,700 stillbirths accounted for 12.2% of the 2.6 million estimated global stillbirths. This suggests that Nigeria still makes substantial contribution to the global burden of stillbirths. This study was conducted to determine the prevalence and identify the causes and factors associated with stillbirth in eight referral hospitals in Nigeria.MethodsThis was a cross-sectional study of all deliveries over a period of 6 months in six general hospitals (4 in the south and 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 19 publications
2
52
2
Order By: Relevance
“…The few documented stillbirth rates in hospitals are usually higher than those estimated in the community (15). Nevertheless, the here reported stillbirth rate with 82 stillbirths /1000 total births is very high in comparison to other countries and hospital reports (15)(16)(17). A large metaanalysis about stillbirth reports from 50 countries showed a variety of causes.…”
Section: Stillbirthscontrasting
confidence: 54%
“…The few documented stillbirth rates in hospitals are usually higher than those estimated in the community (15). Nevertheless, the here reported stillbirth rate with 82 stillbirths /1000 total births is very high in comparison to other countries and hospital reports (15)(16)(17). A large metaanalysis about stillbirth reports from 50 countries showed a variety of causes.…”
Section: Stillbirthscontrasting
confidence: 54%
“…Despite the substantial estimated burden of stillbirths in Nigeria, there is persistent inaccurate data on its predictors to inform appropriate policy interventions. Most studies focus on reporting stillbirth prevalence rates and exploring their clinical determinants [16][17][18][19]. Also, available studies investigated geographic accessibility factors known to strongly influence the use of skilled birth attendant and EmONC for pregnant women but not stillbirth outcome [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Also, available studies investigated geographic accessibility factors known to strongly influence the use of skilled birth attendant and EmONC for pregnant women but not stillbirth outcome [20,21]. Furthermore, existing local stillbirth literature shows substantial regional disparity as they are mainly focused on southern Nigeria [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…According to the latest Nigeria DHS, the maternal mortality ratio is still high at 512 per 100 000 live births (95% confidence interval (CI): 447-578) [11]. Further, the prevalence of stillbirths is estimated at 39.6/1000 births, and 32% of those stillbirths could be associated with asphyxia [12]. A study showed that infants born by CS in Nigeria were roughly three times more likely to die than those born vaginally [13], indicating that the intervention might be used too late.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that infants born by CS in Nigeria were roughly three times more likely to die than those born vaginally [13], indicating that the intervention might be used too late. Other factors associated with increased risk of adverse neonatal outcome during labour in Nigeria include referral status, parity, gestational age [12], male gender and rural residence [13].…”
Section: Introductionmentioning
confidence: 99%